O conhecimento metacognitivo no gerenciamento de impressões: avaliação do uso da falsa modéstia na auto apresentação - Fujie, Márcia Akemi (2021)
Metacognitive knowledge refers to the information that the subject holds about his own cognitive systems and also about cognition in general, being considered as the segment in which the knowledge of the world is stored and the human being is understood as a cognitive creature. It is through this knowledge that the individual controls his resolution behaviors, enabling him to recognize and characterize problem situations, and to choose the resolution strategy that best suits him. Impression management, on the other hand, is the process by which individuals attempt to control their actions in order to adapt to and shape the impressions that others construct about them. One technique recently included in this process is humblebrag, composed of a combination of the strategies humility, complaining, and bragging. However, studies in this field have evidenced that demonstrating sincerity in speech is essential for building a positive image. The main objective of this doctoral dissertation is to investigate evidence of the relationship between metacognitive knowledge and impression management, as well as to examine humblebrag as a self-presentation technique: whether its elements interfere in its process, and if so, which ones. It is first hypothesized that metacognitive knowledge has a direct influence on impression management. The second hypothesis is that humblebrag is moderated by the strategies that compose it, the motivations of self-presentation and the speaker's sincerity and ability to convince. Thus, this thesis is divided into three studies, described in the format of scientific articles. The first manuscript aimed to analyze, by means of a systematic review, studies on impression management and humblebrag. Five references were obtained, the first of which was published in 2015. Main results indicated that complaining and bragging are preferred strategies by the audience when compared to humblebrag. The second manuscript described a pilot study, in which an instrument was developed with the aim of assessing metacognitive knowledge in impression management, and humblebrag and its elements. This instrument was evaluated by three expert judges and applied to 12 university students. Results showed that the instrument is adequate for the constructs it intends to assess. Finally, the third manuscript brought the reformulation of the instrument based on the participants' considerations, and the application of the questionnaire in a representative sample of the instrument's target audience. Results pointed out that during the evaluation of metacognitive knowledge, impression management strategies were indicated, establishing a relationship between the two phenomena. Furthermore, the use of humblebrag, in order to be successful, requires a balance between humble and boastful behavior, and the need to convince the public of one's competence.